El valor alimenticio del sotol - García Sanchez, Alfredo; Alba, Jorge de; Narvaéz, Guillermo L. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
1 be greatest value of sotol (Dasylirion spp) lies in its ability to grow under th extremely avid conditions of Northern Mexico and Southwestern United States. Ther it is utilized as an emergency feed. Ranches that are privileged to bave natural stand: of sotol rely on it to prevent disasters in years of extreme drought The feeding ralne of sotol bulbs on beads was assessed experimentally with both beef and dang cattle the State of Coahuila, Mexico Comparisons were made utilizing old and yerling Hereford females feeding sotol in dry lot, and sotol in uinter pasturage and sorghun silage in dry lot The nation in dry lot was balanced with cottonseed meal, but nо concentrate was given with the sotol on pasture Cou's utilized sotol better than yealings, though yearlings gained more on sorghum silage than on sotol. Old cous uith defective teeth cannot masticate well the fibers of sotol and may easily suffer serions digestive troubles, resulting in death if they are not taken off the sotol diet In the experiment with dairy cous, sotol beads were compared with fresh-cut soiling alfalfa, both fed ad libitum during six hours of barn feeding. A concentrate of 11 digestible protein as used with alfalfa and one of 14% with sotol, both fed at the rate of one kilo of concentrate for each kilo of milk prodmed The test was of the doubl reversal type, with fire cous in each group Highly significant differences were fourd placing de value of sotol for milk production at 77.7 of the value of fresh alfalfa.